From bodily posture to progressive aspect marker - Ismail, Najib (Lingua Posnaniensis, 2015)
The fact that posture verbs tend to grammaticalize into aspectual markers of progressivity in a wide-range of (un)related languages makes them particularly interesting objects of study. The present paper aims to contribute to our understanding of how the active posture participle “yālis” (sitting) plus imperfective verb have come to express the progressive aspect in Emirati Arabic. The proposed answer to this puzzling question involves the claim that, crosslinguistically, progressive constructions are known to originate from locative constructions in which the agent is described as in the midst of an activity. The function of “yālis” (sitting) as an auxiliary verb - like appears to be the result of a grammaticalization process, as certain principles of grammaticalization such as desemanticization, extension, and decategorialization were found to apply to it. Data from Emirati Arabic variety suggest that the construction has undergone semantic and morphosyntatctic changes but retained its phonetic content. As part of the new construction, the active participle “yālis” (sitting) has also changed its argument structure.